2013
DOI: 10.1155/2013/752817
|View full text |Cite
|
Sign up to set email alerts
|

Interval and Continuous Exercise Training Produce Similar Increases in Skeletal Muscle and Left Ventricle Microvascular Density in Rats

Abstract: Interval training (IT), consisting of alternated periods of high and low intensity exercise, has been proposed as a strategy to induce more marked biological adaptations than continuous exercise training (CT). The purpose of this study was to assess the effects of IT and CT with equivalent total energy expenditure on capillary skeletal and cardiac muscles in rats. Wistar rats ran on a treadmill for 30 min per day with no slope (0%), 4 times/week for 13 weeks. CT has constant load of 70% max; IT has cycles of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
1
16
0
2
Order By: Relevance
“…Once again, this suggests that HIIT potentially induced a greater hypoxic stimuli in the contracting muscle. In contrast, previous reports in healthy individuals have shown that capillary density and eNOS content are increased as a result of both ET and HIIT (13,35). However, in a rodent model of Type 2 diabetes, ET preferentially increased the capillarization of oxidative muscles supporting the current interpretation that ET and HIIT have divergent effects in pathological conditions (30).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Once again, this suggests that HIIT potentially induced a greater hypoxic stimuli in the contracting muscle. In contrast, previous reports in healthy individuals have shown that capillary density and eNOS content are increased as a result of both ET and HIIT (13,35). However, in a rodent model of Type 2 diabetes, ET preferentially increased the capillarization of oxidative muscles supporting the current interpretation that ET and HIIT have divergent effects in pathological conditions (30).…”
Section: Discussionsupporting
confidence: 45%
“…Coordinated responses, such as increases in mitochondrial content, elevated maximal activities of oxidative enzyme, and higher expression of plasma membrane transporters, all facilitate a higher oxidative potential of skeletal muscle (11,23,24,38,39,53). In healthy individuals, these adaptations appear to occur independently of the intensity of training, as both high-intensity interval training (HIIT) and moderate-intensity endurance training (ET) induce these responses (7,8,18,19,21,35,36,50,52). These data suggest that HIIT may provide an equally effective and timeefficient alternative to ET.…”
mentioning
confidence: 99%
“…10,11 Preclinical models indicate that regular exercise can increase microvascular density, which seems to be because of the activation of angiogenic mechanisms (described below). 12,13 In addition, regular exercise can increase the diameter of conduit arteries, in part because of enhanced endothelium-dependent vasodilation and increased sensitivity of the vascular smooth muscle to vasodilatory factors. 14,15 Furthermore, a positive remodeling of the conduit arteries because of structural changes in the vessel wall has been described.…”
Section: Vascular Response To Metabolic Demandmentioning
confidence: 99%
“…The increase in the number of mitochondria, the capillary neoformation and the normal activity of myosin ATPase observed in a hypertrophied myocardium by physical exercise, prevent the imbalance between oxygen consumption and supply, and the occurrence of ischemia, unlike observed in pathological hypertrophy [10].…”
Section: Introductionmentioning
confidence: 99%